Clinical and Paraclinical Features of Wilson’s Disease in Children in Shiraz, Southern Iran: - Erjaee, Asma; Dehghani, Seyed Mohsen; Imanieh, Mohammad Hadi; Haghighat, Mahmood; Bajalli, Zohre; Malekpour, Abdorrasoul (Galen Medical Journal, 2014)
Background: Wilson disease (WD) is an autosomal recessive progressive degeneration of hepatolenticular tissue that causes the increase of copper deposition in the liver and other organs, with resultant hepatic, neurologic and psychological manifestations. WD is fatal if left untreated. The aim of the current study was to evaluate the clinical and Para-clinical findings in children with WD in Shiraz, Southern Iran. Patients and Methods: The Medical records of all children less than 18 years of age with definite diagnosis of WD, who were admitted in Nemazee Teaching Hospital from 2001 to 2009, or were under follow up at the Pediatric Hepatology Clinic affiliated to Shiraz University of Medical Sciences, were reviewed. Results: Overall, 70 patients with WD (41 males, 29 females) were studied. The mean age at the onset of diagnosis was 10.3±3.2 years and the most common first presentation in our patients was hepatic (90%). The most common biochemical abnormalities were increased urinary copper content, increased liver enzymes (92.9%), and increased prothrombin time (71.4%). Wilson index was ≥11 in 44.3% of the patients. Conclusion: WD is a rare and fascinating disorder that often poses a diagnostic and therapeutic challenge for the physician. Maintaining a high index of suspicion is critical in diagnosing this readily treatable disease and early treatment can decrease its mortality rate.